Predominant Educational Approaches for Teaching Children with Autism Spectrum Disorder in Primary School - Ališauskienė, Stefanija; Grigėnaitė, Julija (Special Education, 2024)
In inclusive educational practice, three predominant educational approaches differentiation, individualization, and personalization are recognized. These educational approaches are based on inclusive education values, emphasising getting to know the learner and using the most appropriate educational methods, considering the learner’s needs, strengths and interests. In educational practice, these educational approaches are often interchangeable, confused or misinterpreted, leading educators to question when learning and/or teaching is personalised, individualised or differentiated. This article presents exploratory research as part of a broader scientific study. The research aims to identify the educational approaches used by primary school teachers in educating students with autism spectrum disorder (ASD) in an inclusive classroom. The exploratory research is based on a qualitative methodology using a semi-structured interview method. Participants were primary school teachers with experience in teaching learners with ASD (N=8). The study reveals that the education of students, especially those with ASD, is more likely to follow differentiation and individualisation approaches. However, there is also evidence of personalisation in education. The results of the study show teachers’ eagerness to thoroughly understand each student in the classroom; however, there is a prevailing emphasis on the disorder and challenges associated with students with ASD. The characterization of students based on their conformity or non-conformity to norms is a common trait of the individualised education approach. Nevertheless, student cooperation, parental collaboration, teamwork between teachers and student support specialists, recognition of student diversity, and individual understanding of each student all contribute to the essential components of the personalised education concept.The results suggest that the participants in the study combine differentiated, individualised and personalised approaches to educating students with ASD. On one hand, it can be viewed as a flexible integration of various approaches tailored to the learners’ needs and the educational context; on the other hand, it can be seen as an instinctive method used by teachers for addressing educational challenges in the classroom, especially in situations where better theoretical preparation is required.
Keywords: differentiation; individualisation; personalisation in education; autism spectrum disorder; inclusive education